Diagnosis, management and outcome of splenic torsion; a systematic review of published studies. Issue 5 (October 2022) - Bough, Georgina M.; Gargan, Kate E.; Cleeve, Stewart J.; Farrell, Stephen
Abstract: Introduction: Splenic torsion is a rare condition but one that many surgeons will encounter once in their career. Management options are varied but due to the rarity of the condition there are no contemporary evidence-based summaries to inform a treating clinician. We aim to describe patterns of presentation and provide an evidence-based guide to the management. Methods: A PRISMA structured meta-analysis was conducted of all published cases of splenic torsion and a recent case added from our institution. Results: 408 cases were identified between 1888 and 2021 and a single case added from our institution, 312 cases were sourced from case reports and 96 from 40 case series. 8% of patients had a co-existing congenital anomaly and 28% an identified risk factor for splenic torsion. 82% required emergency surgery. A preoperative diagnosis is becoming more common, reaching 80% in 2020's. While spleen conserving surgery is feasible using a variety of techniques. splenectomy was the definitive management for the majority (82%). On histopatholy no occult disease was identified and a significant number of resected spleens were potentially viable; 32% were reported to be normal or congested and 14% demonstrated only partial or focal necrosis. Discussion: Despite the significant publication bias implied by the methodology this is a large dataset in a rare condition. Splenic torsion frequently occurs in a premorbid population. The presence of a palpable mass in the context of abdominal pain should increase suspicion and trigger cross sectional imaging. Conservation of the spleen, using the techniques discussed, should be seriously considered. Highlights: Consider splenic torsion in patients with abdominal pain and a palpable mass. Often presents in patients with ligament laxity, splenomegaly or congenital abdominal anomaly. Not associated with intrasplenic pathology. Splenopexy is feasible and provides an option to save the spleen.